Regional development of Saldanha Bay region, South Africa: The role of Saldanha Steel - Welman, Lesley; Ferreira, Sanette L.A. (Bulletin of Geography. Socio-economic Series, 2014)
Since 1970 the Saldanha Bay region on the West Coast of the Western Cape Province has been high on South Africa’s national development agenda. The region has been struggling for years to meet the preconditions for economic take-off. In this analysis the Saldanha Bay region is positioned in the contexts of global competition among steel-producing countries, South Africa’s national development plan and the Greater Cape Town functional region. The aim is to explain the nature and extent of the relationship between a single secondary industry – ArcelorMittal Saldanha – and the economic development of the larger Saldanha region. Following a brief introduction and background to the Saldanha Bay region, the evolutionary economic geography (EEG) approach and the role of institutions in the development of regions are reviewed. Saldanha Steel (ArcelorMittal), the pioneer industrial firm, is analysed by using a mixed-method approached, where semi-structured interviews and a questionnaire survey are the main research instruments. The contribution of Saldanha Steel to regional development is explored.